2015
DOI: 10.1088/0143-0807/36/6/065004
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking students’ use of mathematics in upper-division physics: where do we go from here?

Abstract: In their study of physics beyond the first year of University -termed upper-division in the US, many of students' primary learning opportunities come from working long, complex back-of-thebook style problems, and from trying to develop an understanding of the underlying physics through solving such problems. Some of the research at the upper-division focuses on how students use mathematics in these problems, and what challenges students encounter along the way. There are a number of different and diverse resea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 68 publications
1
22
0
Order By: Relevance
“…As highlighted in the theoretical background, in research on students' difficulties in mathematics and in physics two main approaches can be distinguished [11,87]: macroscopic studies, aimed at identifying taxonomies of students' difficulties with relevant concepts or tools, and microscopic studies, grounded in theories of knowledge, aimed at describing students' knowledge and cognitive processes in much greater detail. Our study is of the first type.…”
Section: Context and Motivation For The Studymentioning
confidence: 99%
“…As highlighted in the theoretical background, in research on students' difficulties in mathematics and in physics two main approaches can be distinguished [11,87]: macroscopic studies, aimed at identifying taxonomies of students' difficulties with relevant concepts or tools, and microscopic studies, grounded in theories of knowledge, aimed at describing students' knowledge and cognitive processes in much greater detail. Our study is of the first type.…”
Section: Context and Motivation For The Studymentioning
confidence: 99%
“…Using non-Cartesian coordinate systems continues to be difficult for undergraduate physics students [1][2][3] even in upper-division physics courses (e.g., classical mechanics, electromagnetism, thermodynamics, quantum mechanics, statistical mechanics) where application of these mathematical ideas plays a more significant role [4][5][6][7]. As part of a larger initiative into exploring the math-physics interface in upper-division physics courses [8,9], our current collaboration has initiated the development of a research-based curriculum for a mathematical methods course for undergraduate physics majors. This paper discusses a portion of that effort by focusing on the identification of cognitive resources students activate in the context of basis unit vectors, position vectors, and velocity vectors in plane polar and spherical polar coordinate systems.…”
Section: A Background and Purposementioning
confidence: 99%
“…However, education research has shown that many students struggle to apply their acquired mathematical skills in physics contexts [1][2][3][4][5][6][7][8][9][10][11]. Consequently, the investigation of how physics students use mathematics has been a prominent topic in recent literature [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. It is also well established that students have difficulty coordinating information drawn from texts, equations, symbols, graphs, and figures when formulating a solution to a given problem.…”
Section: Introductionmentioning
confidence: 99%